Treatment of wastewater dyeing agent by photocatalytic process in solar reactor - O. Zahraa; S. Maire; F. Evenou; C. Hachem; M. N. Pons; A. Alinsafi; M. Bouchy (International Journal of Photoenergy)
The photocatalytic decolorization of industrial textile dyes has been studied. The treatment was carried out on a solar reactor consisting in a flat active plane, tilted so as to face the sun and to allow the trickling of the water to be treated. Alternatively the reactor could be irradiated by an artificial source. After checking the system using salicylic acid, a conventional model molecule, the photocatalytic decolorization of Orange II, Yellow Drimarene, and Black Drimarene dyes was investigated. Artificial and solar irradiation gave comparable results although the heating by the sun reduced the amount of adsorption. The kinetics agrees with the Langmuir-Hinshelwood model and a discrepancy between adsorption constants deduced from the kinetic and adsorption experiments was interpreted by considering various types of adsorption sites. Orange II and Drimarene dyes decolorization kinetics are opposite limiting cases of the above model, as being of order 0 and 1 with respect to the dye, respectively.